Evaluation of the One Heart Education Program in the Motorcycle Engineering and Business Expertise Competency - Nogi Handepi; Wakhinuddin; Hasan Maksum; Arwizet K (Jurnal Penelitian Pendidikan IPA, 2025)
Vocational education plays a critical role in preparing students to meet industry demands and enter the workforce effectively. This study aims to evaluate the One Heart Education Program in the Motorcycle Engineering and Business expertise competency at SMKN 1 Luak District, focusing on context, input, process, and product aspects, using the CIPP evaluation model. The study examines whether the program has been managed optimally. Employing a mixed-method approach, the research uses purposive sampling, involving 36 respondents, 26 for quantitative data and 10 as qualitative informants. Data collection methods include questionnaires and interviews. The evaluation results show that the program achieved an overall score of 72.24, categorized as sufficient, indicating suboptimal management. In detail, the context aspect related to program objectives is rated as poor, though the environmental aspect is good. The input, process, and product aspects are also found to be lacking. Key recommendations include optimizing the context aspect by refining program goals, adopting a centralized approach in the input aspect to explore students’ potential, enhancing the learning process in the process aspect to better align with industrial standards, and improving outcomes in the product aspect. These improvements aim to enhance the overall effectiveness and impact of the One Heart Education Program.